Microplastics and human health: A scientometric analysis (Research, Society and Development, 2025)
The accumulation of plastics can be seen macroscopically in piles of plastic bottles and bags in landfills, and in a less visible way, microscopically, comprising the microplastics that are everywhere. Our main objective was to evaluate the scientific production on microplastics and human health using the Web of Science database. We focused on estimating the number of publications per year, the most relevant countries in terms of number of publications, highlights of production co-authored within countries, most cited articles, relevant journals in terms of number of publications, and the focus of studies. Seventy-two countries showed scientific production on microplastics and health revealing the importance of the topic throughout the world. The first publications on the subject occurred in Europe and more recently in the Asian countries. The largest number of articles were published by authors from China, but the most cited are from European countries, which were the first to publish on the subject. The journal that ranked first in relevance was the Science of the Total Environment that covers several aspects related to microplastics and human health. Regarding the focus of the studies, the “microplastics in food” category was the one that showed the highest number of publications. From the panorama outlined by our scientometric analysis, a significant increase in publications in recent years is highlighted, gaps are pointed, and paths suggested bettering paving studies on human health and microplastics.